Flexural Strength of Ice on Temperate Lakes: Comparative Tests of Large Cantilever and Simply Supported Beams - Gow,A J; Ueda,H T; Ricard,J A (1978)
Large, simply supported beams of temperate lake ice were found, generally, to yield significantly higher flexural strengths than the same beams tested in the cantilever mode. Data support the view that a significant stress concentration may exist at the fixed corners of the cantilever beams. Maximum effects are experienced with beams of cold, brittle ice substantially free of structural imperfections; for this kind of ice the strength difference factor, here attributed to the effect of stress concentrations, may exceed 2.0; that is, simply supported beams test a factor of 2 or more stronger than the same beams tested in the cantilever mode. In ice that has undergone extensive thermal degradation, the stress concentration effect may be eliminated entirely. Simply supported beams generally yield higher strengths when the top surfaces are placed in tension. This behavior is attributed to differences in ice type; the fine-grained, crack-free top layer of snow-ice which constituted up to 50% of the ice cover in the current series of tests usually reacted more strongly in tension than the coarse-grained crack-prone bottom lake ice. (Author)